Noise of dc-SQUIDs with planar sub-micrometer Nb/HfTi/Nb junctions. (6th July 2015) - Beyer, J; Klemm, M; Storm, J H; Kieler, O; Weimann, T; Morosh, V
Abstract: We have fabricated Nb-based dc-SQUIDs with sub-micrometer planar Nb/HfTi/Nb junctions in order to investigate their noise performance. The SQUIDs are of simple coplanar design, their nominal inductance is ca. 15 pH. Electron beam lithography and chemical-mechanical polishing have been used to realize junctions with cross sections areas as low as about 100 × 100 nm 2 . The SQUIDs exhibit pronounced excess noise increasing towards lower frequencies. This apparent flux noise arises from fluctuations of the junction critical currents or resistances. The Nb/HfTi/Nb junction critical currents are found to be strongly temperature dependent. Upon cooling below ca. 4 K the SQUIDs start to show current–voltage characteristics with negative differential resistances, and their flux noise increases significantly. Estimation of the HfTi barrier electron temperature indicates that the degradation of the SQUID properties towards lower temperature is caused by self-heating effects.